Utilization of a Mobile Multifunctional Workstation for Coronavirus Nasopharyngeal/Oropharyngeal Specimen Collection - Lian, Xiaojing; Zhang, Lili; Zhao, Yang; Li, Yuhua; Jing, Xuemin; Liu, Xin; Han, Jianing; Ma, Jianhong; Zhang, Yongyong; Guo, Huimin; Huang, Xiaojie (Frontiers in Public Health, 2022)
Objectives: To explore the application of mobile multifunctional workstation for COVID-19 sample collection. Methods: Twenty-four nurses and 150 sampled persons involved in throat specimen collection using mobile multifunctional workstation in Beijing Youan Hospital, Capital Medical University, from September 2020 to November 2020, were enrolled in the study as the observation group. Thirty-six nurses and 150 sampled individuals not using workstation from June 2020 to September 2020 as the control group. We compared the two groups: 1) evaluate the satisfaction, safety, convenience, flexibility, collection accuracy，and communication effectiveness for nurses. 2)self-perceived safety, waiting time，and overall satisfaction for sampled persons. Results: The satisfaction scores of nurses in the observation group were significantly higher than those in the control group (P = 0.000), safety(P = 0.034), the convenience (P = 0.001), the flexibility (P = 0.009) and communication effectiveness (P = 0.001); The scores of self-perceived safety (P = 0.049) and overall satisfaction (P = 0.040) of the observation group were higher than those of the control group. Conclusions: The mobile multifunctional workstation for sample collection could improve the sampling environment of nurses, reduce workforce costs and personal protective equipment (PPE), improve the efficiency of sample collection, reduce the risk of infection, and improve nurses and sampled persons satisfaction .